Is There an Acrostic in Balbilla, Epigr. 31 Bernand? - Danielewicz, Jerzy (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
The article presents a critical discussion of the interpretation of one of Balbilla’s epigrams carved on the foot of Memnon’s colossus at Egyptian Thebes (Bernand no. 31) proposed by Marialuigia Di Marzio in her article published in QUCC 2019. According to this interpretation, it contained the acrostic ΕΦΗΩΚΑΕ, which Di Marzio resolves as ΕΦΗ Ω ΚΑΕ(ΣΑΡ), suggesting a direct apostrophe to the emperor Hadrian on the part of the statue. However, there are compelling reasons to reject this intriguing proposal.